Stabilization Mechanism and Safety Control Strategy of the Deep Roadway with Complex Stress - Yang Yu; Dingchao Chen; Xiangqian Zhao; Xiangyu Wang; Lianying Zhang; Siyu Zhu (Advances in Civil Engineering)
With the increase of mining intensity of coal resources, some coal mines in China have gradually entered the deep mining stage. The complexity of the stress environment of the deep rock stratum leads to the difficulty of coal mining. Among them, the control of the deep roadway is one of the bottlenecks restricting the safety mining of the deep coal resources in China. By means of statistical analysis, the factors affecting the stability of the deep roadway were summed up: roadway occurrence environment, driving disturbance, and support means. The mechanical model of the deep roadway was established with the theory of elastic-plastic mechanics, the distribution characteristics of the plastic zone of the roadway were revealed, and the influence laws of lateral pressure coefficient, vertical stress, and support strength on the stability of the roadway were analyzed. Through numerical simulation, the law of stress, displacement and the plastic zone distribution evolution of the deep roadway, the mechanism of horizontal stress, and the mechanism of bolt support on the roadway were studied. On this basis, the safety control strategies to ensure the stability of the deep roadway were put forward: improving the strength of the roof and floor, especially the bearing part of the top angle and the side angle, enhancing the stability of the two sides of the roadway and controlling the floor heave, and making the surrounding rock of the deep roadway release pressure moderately, so as to make the roadway easy to be maintained under the low stress environment. These meaningful references were provided for the exploitation of deep coal resources in China.